2019
DOI: 10.3390/rs11242978
|View full text |Cite
|
Sign up to set email alerts
|

The Scattering Coefficient for Shore-to-Air Bistatic High Frequency (HF) Radar Configurations as Applied to Ocean Observations

Abstract: To extend the scope of high frequency (HF) radio oceanography, a new HF radar model, named shore-to-air bistatic HF radar, has been proposed for ocean observations. To explore this model, the first-order scattering coefficient and the second-order electromagnetic scattering coefficient for shore-to-air bistatic HF radar are derived using the perturbation method. In conjunction with the contribution of the hydrodynamic component, the second-order scattering coefficient is derived. Based on the derived scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Here the Stratton-Chu integral is employed to calculate the scattered field in the far zone of the scattering patch [12,32]. For monostatic configuration, substituting the scattered field from the rough part of the scattering patch into the Stratton-Chu integral gives (26), which represents the scattered field H f (R 0 , t) at the receive antenna.…”
Section: The Scattered Field Far From the Scattering Patchmentioning
confidence: 99%
See 2 more Smart Citations
“…Here the Stratton-Chu integral is employed to calculate the scattered field in the far zone of the scattering patch [12,32]. For monostatic configuration, substituting the scattered field from the rough part of the scattering patch into the Stratton-Chu integral gives (26), which represents the scattered field H f (R 0 , t) at the receive antenna.…”
Section: The Scattered Field Far From the Scattering Patchmentioning
confidence: 99%
“…In (26), H sr denotes the magnetic field corresponding to E sr ; k s = (−k 0 sin θ i , 0, k 0 cos θ i ) is the wave vector of the scatterd field; the square area {…”
Section: The Scattered Field Far From the Scattering Patchmentioning
confidence: 99%
See 1 more Smart Citation
“…The derivation of Johnstone appears to have an error which causes the difference in the resulting expressions; Gill and Walsh followed a more complicated method, however, it has been shown that the monostatic form of their radar cross section is similar to Barrick's and it is, therefore, unnecessary to change the existing operational inversion programs to use theirs instead. Another recent derivation is given in Chen et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…From this discovery, the first-order and second-order Doppler models based on a small perturbation method were established by [6][7][8]. Chen et al [9] analyzed the simulated echo Doppler spectra for various parameters based on a shore-to-air bistatic HF radar model. Subsequently, more investigations focused on microwave bands.…”
Section: Introductionmentioning
confidence: 99%